KEPUASAN NASABAH ATAS LAYANAN E-CHANNEL (Studi Kasus di Bank Syariah Indonesia Provinsi Aceh) - Ulkamila, Annisa; M, Saleh; Azka, Rizkina (Ekonomika Journal, 2024)
This research aims to determine and analyze the influence of BSI e-channel service quality on customer satisfaction in Aceh Province. This research is quantitative in nature with data collection using a questionnaire in the form of Google form. Determining 100 customer samples using purposive sampling. Service dimensions, using factors of reliability, physical evidence, responsiveness, assurance and empathy. Meanwhile, the dimensions of satisfaction variables used are: product and service quality, service quality, emotional, price and cost. And data analysis uses simple linear regression analysis. The research results show that e-channel service quality has a positive and significant effect on BSI customer satisfaction in Aceh Province